A Revised Mental Energy Hypothesis of the g Factor in Light of Recent Neuroscience - Debatin, Tobias (Review of General Psychology, 2019)
The article proposes a revised mental energy hypothesis for the emergence of the g factor. Charles E. Spearman interpreted the g factor as a kind of domain-general mental energy. Nowadays, it is known that the energy currency of organisms is the chemical energy transporter adenosine triphosphate (ATP). ATP is produced by complex metabolic processes (mainly by glucose oxidation), and most of it in the human brain is used for neural signaling. There are substantial individual differences in the metabolic properties of the brain, which lead to different levels of energy production. It is thereby proposed to place more emphasis on individual differences of metabolic functions in intelligence research. Neuroscientific findings suggest that increased brain metabolism and, therefore, higher energy-production levels facilitate better performance on different cognitive tasks. These findings are not in conflict with the refined neural efficiency hypothesis. In addition, building on Dennis Garlick’s proposal that neural plasticity is the core process underlying the development of the g factor, it is illustrated why ATP is crucial for neural plasticity. Taken together, the direct effects of level of energy production on cognitive performance and the relations with neural plasticity suggest an important role in the emergence of the g factor.
CRIS-Team Scopus Importer:2019-05-02
Keywords: energy metabolism; g factor; intelligence; neuroimaging